PERANCANGAN APLIKASI SISTEM ANTRIAN PASIEN POLIKLINIK PENYAKIT DALAM DI RSUD BUDHI ASIH CAWANG JAKARTA TIMUR - Rospita, Ida Putri S; Hosizah, Hosizah; Uddin, Badie (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Budhi Asih Regional General Hospital in Cawang, East Jakarta is a type B+ referral and teaching hospital with a high number of outpatient visits, particularly in the Internal Medicine Polyclinic, which serves an average of 200–250 patients daily. This condition often leads to queue congestion, long waiting times, and patient discomfort. This study aims to design a digital-based queue system application to improve service efficiency, reduce patient congestion, and provide real-time queue information. The research method applied was prototyping, consisting of user requirement identification, initial design, system testing using black box testing, followed by evaluation and revision. Data were collected through observation, interviews with three registration officers, and questionnaires. The results showed that the application performed according to user needs with minor improvements required in the user interface design. The implementation of this system is expected to reduce waiting times, enhance the regularity of service schedules, and support the achievement of hospital minimum service standards in accordance with Ministry of Health regulations. Keywords: Queue System, Prototyping, Black Box Testing, Healthcare Services, Budhi Asih Cawang Regional Hospital Abstrak: RSUD Budhi Asih Cawang Jakarta Timur merupakan rumah sakit rujukan tipe B+ pendidikan dengan jumlah kunjungan rawat jalan yang tinggi, khususnya pada Poliklinik Penyakit Dalam yang rata-rata melayani 200–250 pasien perhari. Kondisi ini kerap menimbulkan kepadatan antrean, lamanya waktu tunggu, serta ketidaknyamanan pasien. Penelitian ini bertujuan merancang aplikasi sistem antrian berbasis digital untuk meningkatkan efisiensi layanan, meminimalkan penumpukan pasien, dan menyediakan informasi antrean secara real-time. Metode penelitian menggunakan pendekatan prototyping dengan tahapan identifikasi kebutuhan (user requirement), perancangan desain awal, pengujian sistem menggunakan black box testing, serta evaluasi dan revisi. Data diperoleh melalui observasi, wawancara dengan tiga petugas pendaftaran, dan kuesioner. Hasil pengujian menunjukkan bahwa aplikasi berjalan sesuai kebutuhan pengguna dengan beberapa perbaikan minor pada tampilan antarmuka. Implementasi sistem ini diharapkan mampu mengurangi waktu tunggu, meningkatkan keteraturan jadwal pelayanan, serta mendukung pencapaian standar pelayanan minimal rumah sakit sesuai regulasi Kementerian Kesehatan. Kata kunci: Sistem Antrian, Prototyping, Black Box Testing, Pelayanan Kesehatan, RSUD Budhi Asih